Role of 'Key Farmer' as 'Opinion Leader’ Through Group Communication in Accepting Farmer’s Innovation in South Sulawesi Cocoa Plantation (Peran ‘Key Farmer’ sebagai ‘Opinion Leader’ Melalui Komunikasi Kelompok dalam Penerimaan Inovasi Petani di Sentra Pertanaman Kakao Sulawesi Selatan) - Bahfiarti, Tuti (Jurnal Pekommas, 2016)
The communications group has a central role in communicating the latest innovations in the field of cocoa. In this study used the term 'farmer' as 'key opinion leader' who served and serve to transfer knowledge through group learning cocoa farmers, especially in South Sulawesi. The purpose of this research is to categorize ' key role farmer' as ' opinion leader ' in accelerating innovation acceptance farmers ranging from planting, maintenance, disease, pests, quality, and innovation is the latest plant cocoa. Type of research uses qualitative descriptive approach which describes the role of the farmer' as ' key 'opinion leader. Results of the study found the group communication 'key farmer’ that serve as ‘ opinion leader' became a source of information from the chairman of the group of farmers who have the level of knowledge, motivation, and understanding a skilled technology and then to transfer knowledge to other members of the farmers group. The key role of the farmer in the group functioning seeking informatio, searching informaton, and utilization information, and dissemination  of agricultural innovations in the field of cocoa, especially in South Sulawesi. The key role of the farmer is called "behavioral information" or information behavior that can motivate the acceptance of cocoa farmers against the latest innovations in the field of cocoa.Komunikasi kelompok memiliki peran sentral dalam mengomunikasikan inovasi-inovasi terbaru di bidang kakao. Dalam penelitian ini digunakan istilah ‘key farmer’ sebagai ‘opinion leader’ yang berperan dan berfungsi mentransfer pengetahuan melalui pembelajaran  kelompok petani kakao, khususnya di Sulawesi Selatan. Tujuan penelitian ini adalah mengategorisasi peran ‘key farmer’ sebagai ‘opinion leader’ dalam mempercepat penerimaan inovasi petani mulai dari cara penanaman, pemeliharaan, penyakit, hama, kualitas, dan inovasi-inovasi terbaru tanaman kakao. Tipe penelitian menggunakan pendekatan kualitatif deskriptif yang menggambarkan peran ‘key farmer’ sebagai ‘opinion leader’. Hasil penelitian menemukan komunikasi kelompok ‘key farmer’ yang berfungsi sebagai ‘opinion leader’ menjadi sumber informasi dari ketua kelompok tani yang memiliki tingkat pengetahuan, motivasi, dan pemahaman teknologi yang terampil kemudian mentransfer pengetahuan kepada anggota kelompok tani lainnya. Peran key farmer dalam kelompok berfungsi mencari informasi pencarian (seeking), penemuan (searching), dan pemanfaatan (using), dan penyebaran (dissemination) inovasi-inovasi pertanian di bidang kakao, khususnya di Sulawesi Selatan. Peran key farmer ini disebut “perilaku informasi” atau information behavioryang dapat memotivasi penerimaan petani kakao terhadap inovasi terbaru di bidang kakao.The communications group has a central role in communicating the latest innovations in the field of cocoa. In this study used the term 'farmer' as 'key opinion leader' who served and serve to transfer knowledge through group learning cocoa farmers, especially in South Sulawesi. The purpose of this research is to categorize ' key role farmer' as ' opinion leader ' in accelerating innovation acceptance farmers ranging from planting, maintenance, disease, pests, quality, and innovation is the latest plant cocoa. Type of research uses qualitative descriptive approach which describes the role of the farmer' as ' key 'opinion leader. Results of the study found the group communication 'key farmer’ that serve as ‘ opinion leader' became a source of information from the chairman of the group of farmers who have the level of knowledge, motivation, and understanding a skilled technology and then to transfer knowledge to other members of the farmers group. The key role of the farmer in the group functioning seeking informatio, searching informaton, and utilization information, and dissemination  of agricultural innovations in the field of cocoa, especially in South Sulawesi. The key role of the farmer is called "behavioral information" or information behavior that can motivate the acceptance of cocoa farmers against the latest innovations in the field of cocoa.